2022
DOI: 10.3390/ijerph192315434
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Scientific Studies on the Effects of Music in People with Personality Disorders

Abstract: Personality Disorders (PDs) are psychiatric conditions involving maladaptive personality traits and behaviours. Previous research has shown that musical preferences and the use of music may be related to personality traits. Additionally, music therapy is increasingly being used as a treatment option for people with PDs. Using the PRISMA guidelines, a systematic literature search was undertaken using three databases: PubMed, Web of Science, and PsycInfo. The following search terms were used: PubMed: “personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The questionnaire titled The Nurse's Knowledge about the Effects of the Tidal Model, Music Therapy, and Mindfulness in Reducing the Exacerbation of Symptoms of Borderline Personality Disorder (BPD) Traits in Puerto Rican Women was administered to 33 participants. The instrument was administered as a pretest to explore their knowledge about the Tidal Model, Mindfulness, and Music Therapy [31][32][33][34][35][36]. It was given as a posttest to verify if they had gained the understanding that would enable them to implement the integration of the approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire titled The Nurse's Knowledge about the Effects of the Tidal Model, Music Therapy, and Mindfulness in Reducing the Exacerbation of Symptoms of Borderline Personality Disorder (BPD) Traits in Puerto Rican Women was administered to 33 participants. The instrument was administered as a pretest to explore their knowledge about the Tidal Model, Mindfulness, and Music Therapy [31][32][33][34][35][36]. It was given as a posttest to verify if they had gained the understanding that would enable them to implement the integration of the approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of its efficacy remains limited, however, due to small sample sizes and methodological limitations. In Haslam et al's (2022) small‐scale systematic review of 24 studies, MT was found to offer a potentially useful treatment option for PDs. The authors reported that selected music helped to reduce violence and hostility; playlists developed by patients with the support of their therapists aided in managing aggressive impulses in foreseeably difficult situations; patients can benefit from music for relaxation; and music can aid cognitive problem solving and improve mood in people with insecurities.…”
Section: Introductionmentioning
confidence: 99%
“…The past few decades have seen increasing research on the psychological aspects of music using behavioral and neural measures (De Witte et al, 2020;McCrary et al, 2022). Even in daily music activities, music training affects attachment patterns and personality characteristics because of its psychological function in arousing/regulating emotion, facilitating cognition, memory recall, and activating sensorimotor functions (Corrigall et al, 2013;Haslam et al, 2022). Correspondingly, the influence of psychological traits on music training has also attracted attention in the contexts of human interaction and human-computer interaction (Penhune, 2020;Miranda, 2021;Tsai and Liang, 2023).…”
Section: Introductionmentioning
confidence: 99%